Criteria for evaluating the work of the internal audit unit for the purposes of financial control of managers of state budget funds - SHCHYRSKA, O. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2022)
The article outlines the essence of the audit processes of state budget managers. The possibility of ensuring high-quality internal audit as a factor in providing information for the purposes of state financial audit and performance audit is considered. The issue of ensuring and implementing such control is the subject of regulatory attention. According to the norms of the current legislation of Ukraine, internal audit must be introduced in the activities of budget funds managers. Such rules apply to managers of state budget funds and local budgets, which ensures the transparency of management of budget funds, management responsibility of managers of different levels, responsibility for ensuring the effective operation of the budget institution. It is stated that in accordance with the current legislation, the external assessment of the quality of the functioning of the internal audit is organized and conducted by the Ministry of Finance of Ukraine. The manager of budget funds in the person of the head forms an independent structural unit of internal audit, subordinated and accountable directly to this head. The main parameters of the work of the internal audit unit are structured, which determine the specifi cs of quality control and the state of internal control of managers of budget funds within the framework of efficiency audit during check ups by the Accounting Chamber and the State Audit Service.